PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN SPONTAN - Edy Purwanto (Journal MISSY (Management and Business Strategy), 2023)
Social media is a tool used by consumers to share various information in the form of images or even videos. The development of online business in Indonesia is very rapid, one of which is shopping online. The variables taken by the researchers are Product, Price, Promotion and Distribution. This research was conducted in order to find out whether there is influence from each variable.This study uses a quantitative method, where the population is the people of Sumenep Regency who have purchased products at Shopee e-commerce. The number of samples used was 110 respondents. The analysis used is multiple linear regression analysis using the SPSS 26 application.The results of this study indicate that Product, Price, Promotion and Distribution simultaneously affect Spontaneous Purchase Decisions in E-commerce Shopee. Based on the results of the t test states that Product, Price and Promotion have a significant effect on Spontaneous Purchase Decisions, while Distribution has no significant effect on Spontaneous Purchase Decisions.